2017
DOI: 10.1002/adom.201700891
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Switchable, Hyper‐Reflective Blue Phase Liquid Crystals Films

Abstract: amorphous phase, whereas BPII and BPI possess double-twisted cylinders arranged in a cubic crystalline structure with simple cubic and body-centered cubic symmetry, respectively. [3,4] BPLCs have attracted people's interest for many potential applications, such as field-sequential displays, [5,6] full-color reflective displays, [7,8] electrically switching devices, [9][10][11][12] tunable photonic crystals, [13,14] phase modulator optical devices, [15][16][17] as well as soft templates for 3D colloidal crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 26 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…The cubic blue phases have been extensively studied in noncross-linked low molar mass systems [20][21][22][23][24][25][26][27] . The primary motivation for these studies is the potential for fast electro-optical switching properties in devices that do not need alignment layers or precise thickness control 28 .…”
mentioning
confidence: 99%
“…The cubic blue phases have been extensively studied in noncross-linked low molar mass systems [20][21][22][23][24][25][26][27] . The primary motivation for these studies is the potential for fast electro-optical switching properties in devices that do not need alignment layers or precise thickness control 28 .…”
mentioning
confidence: 99%
“…Xu et al reported electrically switchable, hyper‐reflective, and fast‐responsive displays based on multilayer BP films containing two single‐layer BP templates with opposite handedness and an interlayer between them ( Figure a,b). [ 156 ] Red, green, and blue films with hyper‐reflectivities of 89, 82, and 68% were obtained by refilling achiral nematic liquid crystals into the multilayer BP templates (Figure 12c). In addition, reflectance switching of the film was realized by the local director reorientation of the liquid‐crystal molecules in a 1 V μm −1 electric field.…”
Section: Stimuli‐driven Bp Photonic Nanostructuresmentioning
confidence: 99%
“…Because the reflection by the CLCs with a helical structure is selective, only circularly polarized incident light with the same handedness as that of CLC is reflected, while light with the opposite handedness is transmitted. Accordingly, for the unpolarized or linearly polarized incident light, the reflectance of a single CLC film is equal to, at most, 50% [11,18]. However, a higher reflectivity of a CLC device is desired to apply in many fields, including reflective display, lasing and mirrors, especially in optical filters.…”
Section: Introductionmentioning
confidence: 99%